Prevention of bronchial fistulas after pneumonectomies for selected cavitary drug resistant lung tuberculosis - Bazhenov, Alexander V.; Mariandyshev, Andrei O.; Hinderaker, Sven G.; Heldal, Einar; Motus, Igor Ya.; Vasilyeva, Irina A. (Frontiers in Surgery, 2023)
Background: The World Health Organization guidelines for management drug resistant tuberculosis include surgery as an additional method in selected cases. Pneumonectomies have higher risk of morbidity, such as bronchial fistulas which may be prevented by bronchial stump covering. We compare two methods of bronchial stump reinforcement. Methods and materials: A retrospective single center follow-up study was done in 52 patients who underwent pneumonectomy for drug resistant pulmonary tuberculosis. Between 2000 and 2017 we performed pneumonectomies with bronchial stump covered by pericardial fat (group 1; n=42), and between 2017 and 2021 the stump was reinforced by pedicled muscle flap (n=10; group 2). Results: Bronchial fistulas occurred in 17/42(41%) of patients group 1 and there was no fistula in group 2, and this was statistically different (Fisher’s test p=0.02). Post-operative complications were seen in 24/42 (57%) of the patients in Group 1, and 4/10 (40%) patients in Group 2 (Fischer’s test p=0.53). In group 1 positive bacteriology decreased from 74% to 24% just after surgery, and in group 2 it decreased from 90% to 10%, but this was not statistically different (Fisher’s test p=0.63). In group 1 no-one died the first month, but 8/42 (19%) died within a year; in group 2 one died within a month, and only this death (10%) within a year. This difference in case fatality was not statistically significant. Conclusions: The use of pedicle muscle flap for bronchial stump coverage during the pneumonectomies for destructive drug resistant tuberculosis can prevent severe postoperative fistulas and improve postoperative life.